Circ-0044539 promotes lymph node metastasis of hepatocellular carcinoma through exosomal-miR-29a-3p - Yi Yang; Xue-Qin Chen; Ya-Xun Jia; Jie Ma; Di Xu; Zuo-Lin Xiang (Cell Death and Disease, 2024)
Abstract Lymph node metastasis (LNM) is a common invasive feature of hepatocellular carcinoma (HCC) associated with poor clinical outcomes. Through microarray profiling and bioinformatic analyses, we identified the circ-0044539-miR-29a-3p-VEGFA axis as a potential key factor in the progression of HCC LNM. In HCC cells and nude mice, circ-0044539 downregulation or miR-29a-3p upregulation was associated with small tumor size, PI3K-AKT-mTOR pathway inactivation, and downregulation of the key LNM factors (HIF-1α and CXCR4). Furthermore, circ-0044539 was also responsible for exosomal miR-29a-3p secretion. Exosomal miR-29a-3p was then observed to migrate to the LNs and downregulate High-mobility group box transcription factor 1 (Hbp1) in Polymorphonuclear Myeloid-derived suppressor cells (PMN-MDSCs), inducing the formation of a microenvironment suitable for tumor colonization. Overall, circ-0044539 promotes HCC cell LNM abilities and induces an immune-suppressive environment in LNs through exosomes, highlighting its potential as a target for HCC LNM and HCC immunotherapy.